Niche construction initiates the evolution of mutualistic interactions. (17th July 2014) - Buser, Claudia C.; Newcomb, Richard D.; Gaskett, Anne C.; Goddard, Matthew R.
Abstract: Niche construction theory explains how organisms' niche modifications may feed back to affect their evolutionary trajectories. In theory, the evolution of other species accessing the same modified niche may also be affected. We propose that this niche construction may be a general mechanism driving the evolution of mutualisms. Drosophilid flies benefit from accessing yeast‐infested fruits, but the consequences of this interaction for yeasts are unknown. We reveal high levels of variation among strains of Saccharomyces cerevisiae in their ability to modify fruits and attract Drosophila simulans . More attractive yeasts are dispersed more frequently, both in the lab and in the field, and flies associated with more attractive yeasts have higher fecundity. Although there may be multiple natural yeast and fly species interactions, our controlled assays in the lab and field provide evidence of a mutualistic interaction, facilitated by the yeast's niche modification.